Layer-by-layer deposition of vesicles mediated by supramolecular interactions - Roling, Oliver (Langmuir : the ACS journal of surfaces and colloids, 2013)
Vesicles are dynamic supramolecular structures with a bilayer membrane consisting of lipids or synthetic amphiphiles enclosing an aqueous compartment. Lipid vesicles have often been considered as mimics for biological cells. In this paper, we present a novel strategy for the preparation of three-dimensional multilayered structures in which vesicles containing amphiphilic β-cyclodextrin are interconnected by proteins using cyclodextrin guests as bifunctional linker molecules. We compared two pairs of adhesion molecules for the immobilization of vesicles: mannose-concanavalin A and biotin-streptavidin. Microcontact printing and thiol-ene click chemistry were used to prepare suitable substrates for the vesicles. Successful immobilization of intact vesicles through the mannose-concanavalin A and biotin-streptavidin motifs was verified by fluorescence microscopy imaging and dynamic light scattering, while the vesicle adlayer was characterized by quartz crystal microbalance with dissipation monitoring. In the case of the biotin-streptavidin motif, up to six layers of intact vesicles could be immobilized in a layer-by-layer fashion using supramolecular interactions. The construction of vesicle multilayers guided by noncovalent vesicle-vesicle junctions can be taken as a minimal model for artificial biological tissue